Self-care educational guide for mothers with gestational diabetes mellitus: A systematic review on identifying self-care domains, approaches, and their effectiveness - Zarina Haron; Rosnah Sutan; Roshaya Zakaria; Zaleha Abdullah Mahdy (Belitung Raya Foundation, Indonesia, 2023)
Background: Gestational Diabetes Mellitus (GDM) is a common form of poor carbohydrate intolerance, prevalent among pregnant women and associated with unhealthy lifestyle behaviors. Given the dearth of information on self-empowerment among mothers with GDM, a self-care health education package needs to be developed to prevent related complications. Objective: This review aimed to identify self-care approaches, domains, and their effectiveness for a proper self-care educational guide package for women with GDM. Design: A systematic review using electronic literature databases published between January 2016 and December 2022 was conducted. Data Sources: Web of Science, Scopus, and Ovid databases were used. Review Methods: This review utilized the PICO (Population, Intervention, Comparison, and Outcomes) framework to screen the retrieved articles for eligibility in which mothers with GDM, educational materials, standard practice or intervention, and effectiveness were considered the PICO, respectively. The CIPP (Context, Input, Process, Product) model served as a framework for adopting the education development model. Mixed methods appraisal tool was used for quality assessment. Data extraction and synthesis without meta-analysis were presented as evidence tables. Results: A total of 19 articles on GDM were included in the final analysis (16 Intervention studies, two qualitative studies, and one mixed-methods study). Four broad domains emerged from the analysis: 1) information or knowledge of GDM, 2) monitoring of blood glucose levels, 3) practice of healthy lifestyles, and 4) other non-specific activities. The majority of the articles employed a face-to-face approach in executing the educational group sessions, and most studies disclosed their positive effects on GDM management. Other methods of evaluating intervention effectiveness were described as improved self-care behavior, increased satisfaction score, enhanced self-efficacy, good glucose control, and better pregnancy outcome. Conclusion: Knowledge or information about GDM, healthy diet, and exercise or physical activity was found to be the most applied domains of intervention. Framework domains based on the present review can be used in the future development of any interventional program for GDM women in enhancing health information reaching the targeted group in promoting self-efficacy. PROSPERO registration number: CRD42021229610.